PENGARUH LIMBAH PADAT PABRIK KELAPA SAWIT DAN PUPUK P TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI(Glycine max L. Merrill) - Samba, Basith Heru; Zuhry, Elza; Yoseva, Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The study aims to observe the effect of palm oil factory solid waste and phosphate fertilizer, and to get the best combination on the growth and production of soybean. The experiment lasted for 3 month from June to August 2017 on experimental garden of Agricultural Faculty of Riau University.The research was carried out experimentally using Randomized Block Design (RBD) factorial which is composed of two factors. The first factor was the palmoil factory solid waste which consists of 3 levels i.e. L0 = without LPPKS, L1 = LPPKS2.5 t. ha-1 and L2 = LPPKS 5 t. ha-1. The second factor that is phosphate fertilizer (P) consisting of 4 levels i.e. P0 = no TSP, P1 = 20 kg P2O5. ha-1, P2 = 40 kg P2O5. ha-1 and P3 = 60 kg P2O5. ha-1. The observed parameters, i.e. plant height, number of primary branches,plant growth rate, harvest age, number of pods per plant, number of seeds per plant, pithy pea percentage,seed weight per m2 and weight of 100 seeds. The data obtained were analyzed using Anova and Duncan on levels 5%. The results showed that giving palm oil factory solid waste enhance the rate of growth of the plant, 100 seed weight and seed weight per m2, whereas the granting of fertilizer P increases the weight of seeds per m2. Granting palm oil factory solid waste 2.5 ton. ha-1 and fertilizer P 40 kg. ha-1 can give you the best results on the weight of seeds per m2.Keywords: soybean, phosphate, Palm Oil factory solid waste.